Activity of the arginase-NO synthase system and changes in the NO system in peripheral blood serum of pregnant women with fetal growth restriction - M.P. Lysyy (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Oxidative stress caused by an increase in reactive oxygen species and/or insufficient availability and activity of antioxidants underlies the modern concept of the pathogenesis of fetal growth restriction (FGR). Oxidative and nitrosative stress do not exist separately, they interact through the formation of peroxynitrite. Therefore, assessment of the nitric oxide (NO) system in clinical settings may be important for the prevention and treatment of FGR. Purpose of the study was to investigate changes in the activity of NO synthase and arginase isoforms in serum of pregnant women with FGR and the impact of these changes on the development of oxidative and nitrosative stress. Materials and methods. The study included the results of the examination of 26 pregnant women with established FGR at the stage of observation in the hospital who made up the first group; the second group included 18 conditionally healthy pregnant women with normal fetal fetometric indicators. All patients had serum NO synthase enzyme activity determined at 37 °C in a 1.5 ml incubation medium. Results. The findings indicate an imbalance between the metabolic pathways of L-arginine in patients with FGR. Changes in the activity of the arginase-NO synthase system enzymes were found in this pathology, which is primarily expressed in an increase in iNOS activity and a decrease in arginase activity. With arginase deficiency, more L-arginine is available for NO synthase, which leads to excessive production of NO. At high concentrations, NO is a factor of endogenous intoxication due to its rapid inactivation with the formation of toxic peroxynitrite. A significant positive correlation between serum peroxynitrite and the sum of nitrites and nitrates, which are stable metabolites of NO, indicates increased NO production and, as a result, higher peroxynitrite levels in pregnant women with FGR. Conclusions. The production of excessive amounts of nitric oxide due to the redistribution of the activity of the NO synthase system towards the Ca²+-independent inducible isoform under conditions of ischemia is the cause of oxidative and nitrosative stress, which play a key role in the pathogenesis of FGR.